CEO CHARACTERISTICS, OWNERSHIP CONCENTRATION AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - NICOLAS BAYU KRISTIAWAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
The study aims at investigating the influence of CEO characteristics on Corporate Social Responsibiliy (CSR) Disclosure and the moderation effect of ownership concentration on the influence of CEO characteristics on CSR disclosure. The sample consist of 93 companies listed in the Indonesian Stock Exchange from 2013 to 2015. The data of CEO characteristics were gathered from the economics and business-related educational background, the functional experience, the gender and the age in the annual reports of the sampled companies and other relevant sources. On the other hand, the data of ownership concentration and of control variable such as company size, financial performance, financial leverage and audit quality were gathered from the BvD Osiris database. The data of CSR disclosure were gathered by means of checklist method on the annual reports of these companies based on the GRI G4 index. The results of the study show that the output functional experience characteristic has positive influence on the level of CSR disclosure. In addition, the moderation test from the ownership concentration on the influence of CEO characteristics on CSR disclosure do not show significant results.